Theoretical and Actual Tourism Penetration Areas in Łódź - Kronenberg, Maciej (Turyzm/Tourism, 2006)
The aim of the article is to compare theoretical and actual tourism penetration areas using the example of Lodz. On the basis of his research, the author draws conclusions regarding the use of theoretical penetration areas in an analysis of tourism penetration space development.